Hubungan Tingkat Pengetahuan Ibu tentang Gizi terhadap Kejadian Stunting pada Balita: The Relationship Between Mother's Level of Knowledge about Nutrition and the Incidence of Stunting in Toddlers - Nickytha Peygirayania Putri; Rizki Muji Lestari; Fitriani Ningsih (Jurnal Surya Medika (JSM), 2022)
Background: The prevalence of stunting in Palangka Raya City based on data from Riskesdas Prov. Central Kalimantan in 2018 had a stunting prevalence of 22,9%, based on data from the Prov. Central Kalimantan in 2019 had a stunting prevalence of 15,0% and based on EPPGBM data from the Palangka Raya City Health Office in 2020, it had a stunting prevalence of 23,97%, so it can be seen that there was a decline in the incidence of stunting in Palangka Raya City from 2018 to 2019 of 7,9 % and an increase in the incidence of stunting from 2019 to 2020 by 8,97%. The purpose: This study aims to determine the relationship between the level of knowledge of mothers about nutrition on the incidence of stunting in toddlers. Methode: This study uses a literature review method. The data source is taken from the Google Scholar database with a range of data years taken from 2017-2020 and used in the Indonesian language. The result: The search results found 6 journals used in this study. From the 6 research journals, researchers found 4 journals that stated that there was a relationship between the level of mother's knowledge about nutrition and the incidence of stunting in toddlers, and 2 journals that stated that there was no relationship between the level of mother's knowledge about nutrition and the incidence of stunting in toddlers. Conclusion: There are 4 journals that state a relationship exists between maternal knowledge about nutrition and the incidence of stunting in toddlers; this is because the majority of respondents have a good level of knowledge. Two other journals stated that there was no relationship between the mother's level of knowledge about nutrition and the incidence of stunting in children under five, this was because the education level of the majority of respondents graduated from elementary school. Stunting can also be affected by food security, low income can affect access to food to meet nutritional needs.